AGRIBISNIS PERIKANAN DI KELURAHAN AIR DINGIN KECAMATAN BUKIT RAYA KOTA PEKANBARU (STUDI KASUS PADA USAHA IKAN SALAI SEDAP) - Yanti Sipahutar; Septina Elida; Wahyu Hamidi (DINAMIKA PERTANIAN, 2019)
ABSTRACT This study aims to analyze the agribusiness subsystem of the "Usaha Ikan Salai Sedap" The results of the study indicated that the applied agribusiness system has been not optimal yet. The production inputs were sufficiently available. Business activities are carried out every day with harvesting 150 kg of Pangasius sp and Clarias sp. The harvesting was done selectively in accordance with the weight of the fish, i.e. 120-140 grams/tail (7-8 tails/kg) for Pangasius sp and 250-300 grams/tail (3-4 tails/kg) for Claria sp. Fresh Pangasius sp and Clarias sp from farming are processed into smoked fish and marketed through marketing institutions. Smoked fish produced from each species (Pangasius sp and Clarias sp) was 37.5 kg each). The added value obtained per kg of raw materials, for Pangasius sp is Rp 7,933.70, and Clarias sp was Rp. 11,760. The profit gained from Pangasius sp and Clarias sp agribusiness for the Pangasius sp and Clarias sp farming activities was Rp 36,297,283.32/process, and Rp 2,233,543.96/process Pangasius sp and Clarias sp for agroindustry activities. Profits from the marketing of Pangasius sp and Clarias sp was as much as Rp 7,419,950. The dominant supporting subsystem in order to support the business activities of the "Usaha Ikan Salai Sedap" agribusiness was financial institutions/banks, counseling, and training.